Efficient adaptive collect algorithms - Afek, Yehuda; De Levie, Yaron (Distributed computing, 2007)
Deterministic collect algorithms are presented that are adaptive to total contention and are efficient with respect to both the number of registers used and the step complexity. One of them has optimal O(k) step and O(n) space complexities, but assumes that processes' identifiers are in O(n), where n is the total number of processes in the system and k is the total contention. The step complexity of an unrestricted name space variant of this algorithm remains O(k), but its space complexity increases to O(n 2). [PUBLICATION ABSTRACT]